Halakhic thinking of Lithuanian rabbis - Pažėraitė, Aušra (Religija ir kultūra, 2008)
1. Lithuanian rabbis have been studying halakhic sources as valuable in themselves, and not just, or not so much for the legal practice. There were rather theoretical religious-legal activities of intellect than activity, based on pragmatic purposes, seeking to regulate religious practices and ethical attitudes. 2. Texts of Lithuanian rabbis reveal that ritual matters, even related to the Second Temple period, were most analyzed and even in the beginning of twentieth century in the search both of solving some of the current halakhic problems, as well as simply analyzing problems purely theoretically. Mainly have been used analytical and analogical methods. 3. As is apparent from examples of commentaries to Halakhot Gdolot by R. Zeev Wolf ben Arye Lipkin (end of 18th–19th c.), also commentaries of Vilna Gaon, Lithuanian rabbis analyzed texts of halakhic authorities carefully and critically, comparing them with the Halakha sources (Talmud, Tosefta), indicating even inaccuracies. 4. Lithuanian halakhic thought, influenced by Vilna Gaon, was characterized by a certain devotion to original texts, sources of the Halakha, whose authority surpassed authority of codex’s of subsequent generations, using critical analytical thinking, principle of analogy, by trusting one’s own reason, that originated from a certain religious attitude. 5. In the book of Chaim of Volozhin, on of the main authors for studying contrasts of hassidic and mitnagdic Thought’s in Lithuania, Nefesh ha-Hayim, is seen a mitnagdic attempt to ground superiority of studying of Torah and Halakha without any pragmatic interest, as the central religious practice, even if based on the same mystical Jewish heritage that served hassidim to develop quite different religious attitudes.
Keywords: Halakha; Lithuanian Halakha; Vilna Gaon; Hayim of Volozhin; analytical thinking